2019
DOI: 10.1111/gcb.14615
|View full text |Cite
|
Sign up to set email alerts
|

Radiative forcing of methane fluxes offsets net carbon dioxide uptake for a tropical flooded forest

Abstract: Wetlands are important sources of methane (CH4) and sinks of carbon dioxide (CO2). However, little is known about CH4 and CO2 fluxes and dynamics of seasonally flooded tropical forests of South America in relation to local carbon (C) balances and atmospheric exchange. We measured net ecosystem fluxes of CH4 and CO2 in the Pantanal over 2014–2017 using tower‐based eddy covariance along with C measurements in soil, biomass and water. Our data indicate that seasonally flooded tropical forests are potentially larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 73 publications
4
54
2
Order By: Relevance
“…This difference could be attributable to vegetation‐mediated transport, which was not captured by most of the studies used to derive the IPCC CH 4 emission factor (Blain et al, ). Our annual NEE‐CH 4 over the natural forest are nevertheless lower than those reported from Amazonian peatlands (Teh et al, ) and floodplain wetlands (Dalmagro et al, ; Pangala et al, ). In Amazonian peatlands, CH 4 production is greater owing to high nutrient status and soil pH, and low recalcitrant carbon (Wassmann et al, ).…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…This difference could be attributable to vegetation‐mediated transport, which was not captured by most of the studies used to derive the IPCC CH 4 emission factor (Blain et al, ). Our annual NEE‐CH 4 over the natural forest are nevertheless lower than those reported from Amazonian peatlands (Teh et al, ) and floodplain wetlands (Dalmagro et al, ; Pangala et al, ). In Amazonian peatlands, CH 4 production is greater owing to high nutrient status and soil pH, and low recalcitrant carbon (Wassmann et al, ).…”
Section: Discussioncontrasting
confidence: 68%
“…We applied two gap-filling approaches (a) mean diurnal course (MDC; Dengel, Levy, Grace, Jones, & Skiba, 2011;Sakabe et al, 2018;Wong et al, 2018) and (b) marginal distribution sampling (MDS; Alberto et al, 2014;Dalmagro et al, 2019;Tang et al, 2018) using the REddyProc package (Wutzler et al, 2018). The MDC is a simple interpolation technique where the missing value is replaced with the averaged value of the adjacent days at exactly that time of day (Falge et al, 2001).…”
Section: Eddy Covariance Data Processingmentioning
confidence: 99%
“…Drought that normally occurs during the dry season in the southern Amazon Basin causes limitations to leaf photosynthesis (Dalmagro et al, ; Dalmolin et al, ) and net CO 2 exchange (Vourlitis et al, ; Zanella De Arruda et al, ), but during El Niño, drought stress becomes more intense and/or prolonged (Panisset et al, ). The 2015–16 El Niño also caused a decline in net CO 2 uptake for a hyperseasonal forest in the PAN (Dalmagro et al, ) and a decline in gross primary production for woodlands in the southern Amazon Basin (Zhu et al, ). Together, these studies indicate that the decline in Δ C w observed for our study sites may have been widespread across the southern Amazon Basin.…”
Section: Discussionmentioning
confidence: 99%
“…WET.PT is thus a seasonal wetland with the WTH near or above the ground level only during wet season. CH 4 emissions occur almost exclusively during the wet season, with inundation acting like a switch (Dalmagro et al, ). In this site, soil respiration and FCH 4 are largely controlled by WTH and soil water content from hourly to weekly timescales (e.g., Johnson et al, ).…”
Section: Methodsmentioning
confidence: 99%